Association of electrocardiogram abnormalities in human immunodeficiency virus infected patients with special reference to QTc interval - Gaharwar, Rakesh; Molke, Swapnil B.; Singh, Ajay Pal; Jatav, O. P. (International Journal of Advances in Medicine, 2017)
Background: Cardiac manifestations of human immunodeficiency virus (HIV) and AIDS are gaining its importance as a reason for increasing morbidity and mortality. A higher prevalence of QT prolongation has been reported among HIV infected patients. However, specific data and clinical evidences are lacking in this regard from the Indian patient population. The objective of this study was to study the ECG abnormalities in HIV patients with special reference to QTc interval. Methods: The study was conducted at the Anti-Retroviral Therapy (ART) Centre of the Department of Medicine, G R Medical College, Gwalior, MP India between March 2012 and November 2013. A total of 130 patients who were HIV positive and either taking antiretroviral therapy or not were included in the study. The patients with history of cardiovascular disease, drugs causing prolonged QTc except antiretroviral therapy were excluded from the study. Detailed history, examination and relevant investigations were done. ECG of all the patients was done and analysed for any abnormality. CD4 count estimation was done. Results: Out of total 130 patients, there were 88 (67.6%) males and maximum (78.4%) no of patients were in age range of 25-44 years. Socioeconomic status of the patients was low, middle and high in 64.6 %, 23.07 and 12.3 % respectively. 77.7% patients were married, 60% were engaged in heavy physical work. ECG was normal in 79 (60.7%) patients, sinus tachycardia in 30 (19 on ART and 11 pre ART patients), LBBB in 4, features of IHD and RBBB in 3 patients each. Prolonged QTc interval was exclusively found in 11 patients (8.46%) who were on ART (p<0.0001). The QTc prolongation was more in patients with lower CD4 count, 6 patients had CD 4 count between 100-150 and 2 were with CD4 count between 150-200. Almost 50% of the patients had CD 4 count <300. Conclusions: ECG was abnormal in 39.2 % HIV positive patients and was more in patients who were on ART. The most common abnormal ECG finding was sinus tachycardia. QTc prolongation was seen in 8.46 % patients and all of them were on ART therapy.